2011
DOI: 10.1038/nrg3031
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing as a tool for Mendelian disease gene discovery

Abstract: Exome sequencing - the targeted sequencing of the subset of the human genome that is protein coding - is a powerful and cost-effective new tool for dissecting the genetic basis of diseases and traits that have proved to be intractable to conventional gene-discovery strategies. Over the past 2 years, experimental and analytical approaches relating to exome sequencing have established a rich framework for discovering the genes underlying unsolved Mendelian disorders. Additionally, exome sequencing is being adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
1,278
2
23

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,526 publications
(1,316 citation statements)
references
References 90 publications
13
1,278
2
23
Order By: Relevance
“…The concerted annotation and splicing analysis of novel exons have deep implications for the detection and interpretation of human disease (Bamshad et al , 2011; Gonzaga‐Jauregui et al , 2012; Xiong et al , 2015; Bowdin et al , 2016). For one, exome and panel sequencing remains the method of choice for the detection of genetic diseases and both methods rely on current exon annotations (Chong et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The concerted annotation and splicing analysis of novel exons have deep implications for the detection and interpretation of human disease (Bamshad et al , 2011; Gonzaga‐Jauregui et al , 2012; Xiong et al , 2015; Bowdin et al , 2016). For one, exome and panel sequencing remains the method of choice for the detection of genetic diseases and both methods rely on current exon annotations (Chong et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Currently available NGS platforms are powerful and flexible, and can be adapted easily to the analysis of a single gene region in thousands of samples, or for sequencing the entire genome of a single patient. The implementation of NGS has been a paradigm shift in genetics research and is now considered the gold standard for genetic diagnosis 12,13 . NGS has also been widely embraced by the fields of cancer and hereditary diseases.…”
mentioning
confidence: 99%
“…23,48 Laboratories performing clinical MPS testing should ensure that proper evidence is in place to classify the variant as pathogenic, such as cosegregation data, the lack of a variant in healthy family members in published reports, the absence or small representation of the variant in large control data sets (e.g., dbSNP, Exome Variant Server, and ExAc Browser), and in vitro data that show aberrant gene function. 42,[49][50][51][52][53][54][55] Many variants that have previously been reported as pathogenic in the medical literature (and thus are represented in databases used for molecular DNA analysis) are now known to have allele frequencies that make them very common occurrences in the general population, or they have been seen in the homozygous state in healthy controls. [56][57][58] Large polymorphic genes, such as the ABCA4 gene associated with Stargardt disease, arRP, autosomal-recessive CRD, and cone dystrophy, are likely to contain more variants that require scrutiny because some variants may have been previously erroneously asserted as being pathogenic.…”
Section: Variant Interpretationmentioning
confidence: 99%
“…49,61 By searching for variants in known positive controls, Audo et al 31 studied the robustness of NGS panels and found lower coverage for two genes associated with congenital stationary night blindness, NYX (OMIM 300278) and GRM6 (OMIM 604096), as a result of GC-rich regions. In addition, because of low coverage of the PRPF31 gene, a known one-base pair deletion was undetectable.…”
Section: Limitations Of Mps Testingmentioning
confidence: 99%